+0  
 
0
94
2
avatar

y= -3x + 5 

5x - 4y = -3

 Feb 3, 2021
 #1
avatar+268 
+1

The question tells us the value of y which is -3x +5

So we can substitute that with y in the 2nd equation.

 

5x - 4y= -3

5x -4(-3x + 5) = -3

5x + 12x - 20 = 3

17x = 23

x= 17/23

 

Hope that helps! :)

 

🙃🙃👌

 Feb 3, 2021
 #2
avatar+267 
+2

FOR X: substitute -3x+5 in terms of y and add 20 to both sides and divide both sides by 17 to get x=1

 

FOR Y: substitute 1 in terms of x and simplify to get y=2

 Feb 4, 2021

28 Online Users

avatar
avatar
avatar
avatar
avatar
avatar
avatar